COMPARISON OF CONVENTIONAL AND ULTRASOUND GUIDED PREOPERATIVE ASSESSMENT OF AIRWAY TO PREDICT DIFFICULT LARYNGOSCOPY AND INTUBATION - Dr Veena Chatrath; Dr Ranjana Khetarpal; Dr Gagandeep Kaur; Dr Amanat Kaur Virk (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND: Advance prediction of difficult airway provides us ample time for optimal preparation and participation of experienced anesthesiologist. The present study was designed to evaluate the efficacy of clinical and ultrasound guided parameters to predict difficult intubation.MATERIAL AND METHOD: This prospective, observational, double blind study was conducted on 100 patients, aged 18-65 years of ASA grade I, II and III scheduled for elective surgery under general anesthesia. Airway assesment was done preoperatively using clinical parameters (Mallampati score, Thyromental distance (TMD), Hyomental distance ratio (HMDR), Upper Lip Bite Test (ULBT) and ultrasound guided parameters (skin to anterior commissure distance (ANC-VC), tongue volume (TV), Hyomental distance ratio (HMDR), skin to epiglottis distance (DSE) to predict difficult intubation. Findings of the screening tests were corelated with the findings of cormack lehane grading on laryngoscopy and their sensitivity, specificity, positive predictive value, negative predictive value and area under ROC curve was calculated to predict difficult airway. Number of attempts taken for intubation, time taken for intubation and failed intubation was noted. RESULTS: The incidence of difficult intubation was 20%. Among clinical parameters HMDR has sensitivity of 81.82%, specificity of 97.44% with positive predictive value (PPV) of 95% and negative predictive value (NPV) of 90% with AUC of 0.888. however, ULBT has highest NPV of 96.25%. Among USG guided parameters DSE has sensitivity of 97.50% and specificity of 98.73% with PPV of 97.50% and NPV of 95% with AUC of 0.992.CONCLUSION:   Hyomental distance ratio as a clinical parameter was a good predictor of difficult airway with high area under ROC curve with good sensitivity and specificity. However, Ultrasound guided parameters have an edge over clinical parameters as ultrasound guided skin to epiglottis distance was more accurate for predicting difficult airway.